2005
DOI: 10.1042/bst0330428
|View full text |Cite
|
Sign up to set email alerts
|

Haemostasis in normal pregnancy: a balancing act?

Abstract: Pregnancy is a risk factor for venous thrombosis and the incidence of venous thromboembolism during normal pregnancy is 6-fold higher during pregnancy than in the general female population of child-bearing age. This incidence is, however, remarkably low given the increases in markers of haemostatic activation observed during normal pregnancy. During normal healthy pregnancy there are substantial changes in the haemostatic system, many of which are procoagulant and supposed to be in preparation for the haemosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 43 publications
3
63
2
4
Order By: Relevance
“…9 These findings are consistent with the increase in coagulation factors and platelet reactivity and the decrease in endogenous anticoagulant activity that accompany pregnancy. 1 Furthermore, the baseline TEG values in our study groups are similar to those reported by Macafee et al who assessed normal TEG values in a healthy cohort undergoing elective CD under spinal anesthesia; the mean (SD) age of women in this study was 34 (4.1) yr. 10 We observed evidence of time-dependent changes in the maternal coagulation profiles of AMA and non-AMA women. In both groups, statistically significant, yet modest, decreases in G (shear elastic modulus) values were observed at 24 hr post-CD compared with preoperative values.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…9 These findings are consistent with the increase in coagulation factors and platelet reactivity and the decrease in endogenous anticoagulant activity that accompany pregnancy. 1 Furthermore, the baseline TEG values in our study groups are similar to those reported by Macafee et al who assessed normal TEG values in a healthy cohort undergoing elective CD under spinal anesthesia; the mean (SD) age of women in this study was 34 (4.1) yr. 10 We observed evidence of time-dependent changes in the maternal coagulation profiles of AMA and non-AMA women. In both groups, statistically significant, yet modest, decreases in G (shear elastic modulus) values were observed at 24 hr post-CD compared with preoperative values.…”
Section: Discussionsupporting
confidence: 76%
“…1 Pregnant women are at increased risk for venous thromboembolism (VTE), a leading cause of pregnancy-related maternal death in developed countries. 2,3 In several population-wide studies, advanced maternal age (AMA) has been associated with an increased risk of pregnancy-related VTE; [4][5][6] however, the pathophysiological basis that explains why AMA women are at increased risk of VTE compared with non-AMA women has not been adequately investigated.…”
Section: Résumémentioning
confidence: 99%
“…These changes accorded with a report of Urasoko et al (2009). In addition, factor VII and X activities were significantly activated as reported in pregnant women (Franchini, 2006;Holmes and Wallacet, 2005;Brenner, 2004). In non-treated lactating rats, a decrease of ATIII value was observed.…”
Section: Discussionmentioning
confidence: 58%
“…During pregnancy, it is well known that significant changes are observed in blood parameters including those related to blood coagulation system in rats and rabbits (Mizoguchi et al, 2009;Urasoko et al, 2009;Honda et al, 2008;de Rijk et al, 2002;Katoh et al, 1992;Wells et al, 1999) as well as in women (Franchini, 2006;Holmes and Wallacet, 2005;Brenner, 2004). Therefore, the reaction to chemical exposure is possibly different between pregnant or postpartum animals and non-pregnant animals.…”
Section: Introductionmentioning
confidence: 99%
“…TFPI has been found in amniotic fluid as well 20 , but it is not clear if the presence of TF and its natural inhibitor is related to coagulation per se or is somehow connected with embryonic development 24 . In contrast to the changes detected in the amniotic fluid and the decidua, the median maternal plasma immunoreactive TF concentration of normal pregnant women do not differ significantly from that of non-pregnant patients 3,25 . However, labor at term increases significantly the maternal plasma immunoreactive TF concentration in comparison to the non-pregnant state 20 .…”
Section: What Are the Changes In The Coagulation System During Normalmentioning
confidence: 57%